Pemodelan Kanvas Preposisi Nilai Produk Minuman Fungsional untuk segmen konsumen generasi Z dan Y - Adila Sosianika; Rafiati Kania; Fatya Alty Amalia (Jurnal Bisnis dan Kewirausahaan)
The COVID-19 pandemic has motivated many people to consume functional beverages to live a healthy life. One of the instances for functional beverages is fruit juice, which has higher economic value than only sold as an original fruit without any further processing. Despite people showing a higher interest in consuming fruit juice since the pandemic, they cannot entirely abandon their old preferences by consuming high-sugar sweet drinks. However, they can be at risk of chronic diseases in the future. Generation Y and Z are the consumer segments who still rarely consume functional beverages than older segments. They seem to fail to recognize the value of functional beverages. This study aims to pinpoint the Customer’s Value Proposition of Functional Beverages covering Products/Services, Gain Creators,and Pain Relievers that must fit the Customer Segments. To identify the value proposition, this study conducted in-depth interviews with 15customers of functional beverages. The findings claim thatyoung consumers consider functional beverages based on their nutritional content, taste, aroma, packaging, ease of consumption, branding, benefits, and price. Thus, based on the findings, functional beverage enterprises can create a better value-creation strategy for young customers.